Applications of graphene nanomaterials in energy storage—a state-of-art short review - Farhana, Kaniz; Kadirgama, Kumaran; Subramonian, Sivarao; Ramasamy, Devarajan; Samykano, Mahendran; Mahmude, Abu Shadate Faisal (2023)
The study presents the usage behavior of graphene in the energy field. Graphene has been comprehensively studied in the energy-related application due to higher conductivity and mechanical flexibility. The architecture of graphene permits